Individuals with musculoskeletal conditions awaiting orthopaedic surgery consultation: an untapped opportunity for patient health management? - Simon RE Davidson; Emma Robson; Kate M O'Brien; Steven J Kamper; Robin Haskins; Pragya Ajitsaria; David Dewar; Christopher M Williams; Population Health Working Group (Sax Institute, 2024)
Objective: To describe the health characteristics, condition-specific measures, chronic disease risk factors, and healthcare and medication use over time of individuals with musculoskeletal conditions awaiting orthopaedic surgical consultation. Study importance: Musculoskeletal conditions are highly prevalent in the general population and often coexist with chronic diseases. However, little is documented about the overall health of this group. This study describes the health of these individuals, with particular emphasis on modifiable risk factors of chronic disease. Study type: A repeated measures longitudinal cohort study of individuals referred for orthopaedic consultation across three time points (2014, 2015 and 2016). Methods: This study was undertaken in the orthopaedic outpatient service of a public tertiary referral hospital in New South Wales, Australia. Participants were aged 18 years and older and were referred for and awaiting orthopaedic surgical consultation for a musculoskeletal condition (back, neck, hand or wrist pain, or hip or knee osteoarthritis). Measures included patient demographics, condition-specific indicators (e.g. pain, disability, quality of life [QoL]) and chronic disease risk factors (e.g., excess weight, smoking). Results: The mean age of participants was 57.7 years, and 7.3% identified as Aboriginal and/or Torres Strait Islander. Back (43.1%) and knee (35.0%) pain were the most prevalent conditions. At baseline (N = 1052), participants reported moderate pain (mean numerical pain rating scale score of 6.4, standard deviation [SD] 2.4) and QoL (Physical Component Score of 32.7, SD 10.7; Mental Component Score of 46.6, SD 13.3). Chronic disease risk factors were highly prevalent, with 74.6% of participants having three or more. For most measures, there were only small changes over time. Conclusion: Individuals with musculoskeletal conditions who are awaiting orthopaedic surgical consultation have a complex clinical picture and numerous chronic disease risk factors. Given the modifiable nature of many of these risk factors, identifying and addressing them before or while awaiting consultation may improve the health of these individuals.